(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Ephedra foliata Boiss, family Ephedraceae, a gymnosperm shrub, It bears dioecious flowers and semi-transparent berry like fruits. Dried stems are used to cure bronchitis, asthma, influenza and hay fever. The seeds were treated with 0.4 Bavistin, 0.2 streptomycin and 0.1 HgCl2 and cultured on full and half strength MS medium supplemented with different concentration of GA3, BAP, Kinetin and NAA alone and in combinations. Within the range evaluated, highest percentage (55 and 30) of the seed germination was obtained with MS half strength medium containing 2mgl-1 GA3 and combination of 2mgl-1 BAP + 0.2mgl-1 Kinetin after 3 weeks of inoculation. No germination was observed from seeds cultured on MS full strength medium. The seeds were unable to germinate on vermiculite. The present study first time reveals the in vitro seed germination protocol for this plant.